The beneficial effects of Tartary buckwheat (Fagopyrum tataricum Gaertn.) on diet-induced obesity in mice are related to the modulation of gut microbiota composition - Yiming Zhou; Haoyu Lu; Shen Zhao; Beibei Yan; Hong Wang; Xiaoli Zhou; Ying Xiao (Food Science and Human Wellness)
The gut is home to a large number of intestinal microbiota that play an important role in the metabolism and immune system of the host. A growing body of evidence suggests that a high-fat diet is closely associated with many metabolic disorders, including fatty liver and type 2 diabetes. According to reports, Tartary buckwheat extract has a positive effect on intestinal microbiota in animals. The effects of Tartary buckwheat on biochemical indexes and intestinal microflora in mice were studied. Tartary buckwheat protein (FGP), Tartary buckwheat resistant starch (FGS) and Tartary buckwheat flour (FGF) alleviated organ damage in mice and lowered the atherosclerotic index (AI) in plasma. Otherwise, principal coordinate analysis (PCoA) showed that intestinal bacterial structure of FGF were separated apparently from other groups. The Firmicutes/Bacteroidetes (F/B) value of the high-fat (HF)-FGF group was significantly lower than that of the HF-FGP and HF-FGS groups. FGF significantly increases the abundance of beneficial bacteria such as Bifidobacterium, while decreasing the abundance of lipopolysaccharide (LPS)-producing bacteria. Observation of blood lipid metabolism parameters and analysis of the intestinal microbiota suggested that FGF can be more effective than FGP and FGS to reduce the effects of a high-fat diet in mice, restoring the blood parameters to values similar of those in mice fed a low-fat diet. FGF may be used to prevent or treat blood lipid metabolism disorders and intestinal microbiota disorders in mice fed a high-fat diet.